2023
DOI: 10.1186/s12877-023-03851-z
|View full text |Cite
|
Sign up to set email alerts
|

Nonagenarians admission and prognosis in a tertiary center intensive coronary care unit – a prospective study

Abstract: Background With increasing life expectancy, the prevalence of nonagenarians with cardiovascular disease is steadily growing. However, this population is underrepresented in randomized trials and thus poorly defined, with little quality evidence to support and guide optimal management. The aim of the present study was to evaluate the clinical management, therapeutic approach, and outcomes of nonagenarians admitted to a tertiary care center intensive coronary care unit (ICCU). … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Previous studies 6 , 16 have reported in-hospital mortality rates for nonagenarians admitted to the CCU of 5.6% and 15%, with 1-year mortality rates of 30% and 47%; in the present study, these percentages were 5.6% and 19%, respectively. The independent predictors of long-term outcomes among nonagenarians have been reported to be pulmonary hypertension, diabetes, Elder Risk Assessment score, the Acute Physiology, Age, and Chronic Health Evaluation (APACHE) III score, diastolic blood pressure, blood urea nitrogen, inotrope use, and a recent emergency department visit.…”
Section: Discussionsupporting
confidence: 46%
See 4 more Smart Citations
“…Previous studies 6 , 16 have reported in-hospital mortality rates for nonagenarians admitted to the CCU of 5.6% and 15%, with 1-year mortality rates of 30% and 47%; in the present study, these percentages were 5.6% and 19%, respectively. The independent predictors of long-term outcomes among nonagenarians have been reported to be pulmonary hypertension, diabetes, Elder Risk Assessment score, the Acute Physiology, Age, and Chronic Health Evaluation (APACHE) III score, diastolic blood pressure, blood urea nitrogen, inotrope use, and a recent emergency department visit.…”
Section: Discussionsupporting
confidence: 46%
“…14 Although issues regarding elderly patients in the ICU/CCU are universal, there are few studies to date that have directly addressed octo- and nonagenarians in the CCU. 6 , 15 , 16 As such, details, outcomes, predictors, and the cost-effectiveness of treating elderly patients in the CCU require further investigation. Bruoha et al reported that, among nonagenarians, there was a higher proportion of females and patients with hypertension, cerebrovascular accident, congestive heart failure, AF, and anemia, and lower BMI and albumin values, 6 which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations